2019
DOI: 10.1051/bioconf/20191501036
|View full text |Cite
|
Sign up to set email alerts
|

VitiMeteo and Agrometeo: Two platforms for plant protection management based on an international collaboration

Abstract: The negative effects of plant protection products on the human health and the environment have become a major concern for consumers and politics in Europe. In the last years new policies for risk mitigation and reduction of use of synthetic pesticides has been enforce in Europe and Switzerland. A possible strategy to reduce the use of plant protection products is to spray according to the epidemic of diseases and pests by following decision support systems (DSS). The platform VitiMeteo offers a wide set of for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…However, in order to provide reliable predictions, DSS depend on accurate and reliable data provided by local and fully maintained weather stations. One well established decision support system in viticulture which combines several models for diseases, pests, and phenology is VitiMeteo (VM) [ 13 ]. VitiMeteo was introduced in 2002 and has now been evaluated in vineyards throughout Baden-Wuerttemberg (Germany) for almost two decades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in order to provide reliable predictions, DSS depend on accurate and reliable data provided by local and fully maintained weather stations. One well established decision support system in viticulture which combines several models for diseases, pests, and phenology is VitiMeteo (VM) [ 13 ]. VitiMeteo was introduced in 2002 and has now been evaluated in vineyards throughout Baden-Wuerttemberg (Germany) for almost two decades.…”
Section: Discussionmentioning
confidence: 99%
“…Valuable tools for integrated plant protection and the reduction of treatments are decision support systems (DSS), e.g., Agrometeo.ch [ 10 ], vite.net [ 11 ], or VitiMeteo [ 12 ]. Combining real time weather data, weather forecast models, and specific algorithms, the well-established DSS VitiMeteo provides predictions of the development of the most important diseases and pests in viticulture in several winegrowing countries in Europe [ 13 ]. Based on predicted infection events and the calculated development of plant growth, winegrowers are able to decide whether a treatment is necessary or not.…”
Section: Introductionmentioning
confidence: 99%
“…The infection process needs a minimum of 13° C plus 8 mm of rain to occur [ 16 ]. This prerequisite enables precise forecasting, especially for the primary infection [ 11 ]. After primary infection and through the incubation time, germinated sporangia produce many zoospores, which may cause secondary infections on nearby plants.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the weather station data, the model calculates and predicts the potential infection risk with sporulation and incubation times for specific viticultural regions [ 9 ]. Several studies [ 6 , 10 , 11 ] showed that the prediction of the model is relevant to practice and is highly correlated to real occurrences of infection with accuracy increasing annually. Nevertheless, the precisions of the models have some variations to be minimised.…”
Section: Introductionmentioning
confidence: 99%
“…Some commercial solutions that use modern low-power technologies such as LoRaWAN or NB-IoT, have recently emerged (e.g., Metos [13]). Two examples of a platform-based approach consist of a weather station net, disease models, and the Internet website with specific tools and features [27]. A new line of research suggests using a machine learning approach to downy mildew forecasting [28].…”
Section: Related Workmentioning
confidence: 99%